Kelemahan Pendidikan Karakter pada Remaja Indonesia - Adi Suryanto; Saliman Saliman; Sudrajat Sudrajat (Jurnal Penelitian Pendidikan IPA, 2023)
Natural Science plays an important role in developing student character to form superior and noble human resources. This study aims to identify the weaknesses of character education for adolescents in Indonesia.The components that are the focus of evaluating character education learning consist of character education program policies in schools, lesson planning, learning implementation, monitoring and results of implementing character education learning. The research samples were 309 students, 306 parents, and 40 teachers. Data collection techniques using questionnaires and documentation. The collected data will be analyzed using descriptive statistics. The results of the study show that schools have implemented character education in a good category in accordance with the character education policies set by the government. 53%-75% of teachers are in good standing. Parents and students have the same perception of the implementation of character education in schools that character education can be implemented properly in schools. Character education has been running but not optimal, there are still several aspects that need to be addressed such as the preparation of lesson plans for mathematics, science, Indonesia language, and social studies as well as mentoring the implementation of character education. The teacher's ability to integrate character values ​​into lesson plans needs to be improved. Recommendation: Character education should be continued by increasing teacher commitment and performance